(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Actions involving the crime of child pornography are typified in articles 240 et seq. of the Child and Adolescent Statute. Just like other forms of child sexual abuse, victims of child pornography can be of any gender, color or social class. There are reports that there is an increasing recruitment of socially vulnerable minors to serve as victims in this type of crime. The purpose of this article is to discuss whether the socioeconomic situation of children and adolescents is decisive for a minor to become a victim of child pornography. To this end, scientific articles and documents related to the topic were analyzed, as well as newspaper articles and news that link child pornography to poverty.